Human Cellular Nucleic Acid-Binding Protein Zn(2+) Fingers Support Replication of Human Immunodeficiency Virus Type 1 When They Are Substituted in the Nucleocapsid Protein - McGrath, Connor F. (American Society for Microbiology, 2003)
A family of cellular nucleic acid binding proteins (CNBPs) contains seven Zn(2+) fingers that have many of the structural characteristics found in retroviral nucleocapsid (NC) Zn(2+) fingers. The sequence of the NH(2)-terminal NC Zn(2+) finger of the pNL4-3 clone of human immunodeficiency virus type 1 (HIV-1) was replaced individually with sequences from each of the seven fingers from human CNBP. Six of the mutants were normal with respect to protein composition and processing, full-length genomic RNA content, and infectivity. One of the mutants, containing the fifth CNBP Zn(2+) finger (CNBP-5) packaged reduced levels of genomic RNA and was defective in infectivity. There appear to be defects in reverse transcription in the CNBP-5 infections. Models of Zn(2+) fingers were constructed by using computational methods based on available structural data, and atom-atom interactions were determined by the hydropathic orthogonal dynamic analysis of the protein method. Defects in the CNBP-5 mutant could possibly be explained, in part, by restrictions of a set of required atom-atom interactions in the CNBP-5 Zn(2+) finger compared to mutant and wild-type Zn(2+) fingers in NC that support replication. The present study shows that six of seven of the Zn(2+) fingers from the CNBP protein can be used as substitutes for the Zn(2+) finger in the NH(2)-terminal position of HIV-1 NC. This has obvious implications in antiviral therapeutics and DNA vaccines employing NC Zn(2+) finger mutants.